Should irregular migrants have the right to healthcare? Lessons learnt from the Spanish case. (May 2016) - Boso, Àlex; Vancea, Mihaela
This article critically evaluates the Royal Decree-Law 16/2012, which regulates migrants' access to public healthcare services in Spain. In particular, it examines the political rationale behind the restriction of migrants' access to primary and specialised healthcare services. We depart from the right to health as it is defined in the Spanish and international legislations to deconstruct three arguments used by the Popular Party government – the administrative status, high health costs and possible pull effect of welfare policies – to legitimise irregular migrants' exclusion from full medical coverage. We contend that the Royal Decree-Law 16/2012 not only fails to meet the requirements of a human rights based approach but it may also be economically inefficient in the medium to long term.